Umbilical artery Doppler indices in relation to fetal outcome in high risk pregnancy - L., Rashmi; Bhattacharjee, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Umbilical artery Doppler indices in relation to fetal outcome in high risk pregnancy. The aim of this study was to study the umbilical artery Doppler velocimetry in predicting the fetal outcome in high risk pregnancy. This is a prospective study done over a period of 1 year in Silchar Medical College and Hospital from 1st September 2011 to 31st August 2012. 100 women with singleton pregnancy with high risk admitted in SMCH were subjected to umbilical artery Doppler along with morphology and biometry scan after fulfilling the inclusion and exclusion criteria. Methods: 100 women with high risk pregnancy were evaluated by umbilical artery velocimetry between 28 and 41 weeks of pregnancy. Outcome of pregnancy was recorded for the normal Doppler group (n = 79; 79%), the low-end diastolic flow group (n = 19; 19%) and the group with absent/reversed diastolic flow (n = 2; 2%). Results: Mothers with abnormal velocimetry had more number of caesarean sections than those with normal velocimetry. The diagnosis to delivery interval, gestational age at delivery and average birth weight were comparatively lower with higher incidence of admission to neonatal intensive care unit in foetuses with abnormal umbilical Doppler velocimetry. Sensitivity, specificity, positive and negative predictive values of Doppler for detecting abnormal fetal outcome were 43%, 83%, 33% and 88% respectively. Statistical analysis used: sensitivity, specificity and predictive values. Conclusions: Fetuses with normal flow velocimetry are at lower risk than those with abnormal velocimetry in terms of poor Apgar score and neonatal intensive care admission. The average birth weight of the neonates with abnormal Doppler studies was lower than that of neonates with normal velocimetry. Doppler velocimetry studies of umbilical artery can provide the obstetrician important information regarding fetal wellbeing to help him improve fetal outcome.